NUTRITCIOGENETICS AND RISK FACTORS OF CARDIOVASCULAR DISEASE: ASSOCIATED RESEARCH IN EASTERN SIBERIA POPULATIONS - T. A. Bairova; V. V. Dolgikh; L. I. Kolesnikova; O. A. Pervushina (Acta Biomedica Scientifica, 2013)
Purpose: to study nutritional habits as a risk factor of cardiovascular pathology as so as a role of apolipoprotein A1 gene in metabolism in native and alien population of Eastern Siberia. Methods: we used Kiselev questionnaire (1998) for estimation of "nutritional risk". Totally 863 adolescents were evaluated, including 445 (51,6 %) persons of the alien ethnogroup (Russian) and 418 (48,4 %) persons of the native ethnogroup (Buriat). We evaluated clinically, functionally and genetically healthy and hypertensive (having essential arterial hypertension) adolescents and compared the results. Out of 226 adolescents with essential arterial hypertension, 144 persons were from the alien ethnogroup (mean age is 16,22 ± 1,14 years) and 82 adolescents from the native ethnogroup (mean age is 16,57 ± 1,62 years). Out of 173 healthy adolescents (mean age is 15,12 ± 2,71 years), 79 (45,7 %) persons were buriats and 94 (54,3 %) persons were Russian. Ethnic data were gotten by questionnaire, which included information about nationality back to the third generation of ancestors. We studied a total genomic DNA, which was extracted from blood serum by non-enzymatic method. An amplification of DNA loci was performed by polymerase-chain reaction using an automatic thermocycler «Biometra» with «SNP-экспресс», «Litex» reagents. The results of our research indicated an imbalance of nutritional habits with domination of protein-lipid dietary compounds in adolescents of native and alien population ofEastern Siberia. We found differentiated contributions ofinsertion-deletional polymorphism of apolipoprotein A1 gene. We did no found differences of frequency response of alleles and genotypes. We found a positive linkofapolipoprotein Al gene deletion with increased level ofcholesterine, very low density lipoproteins, triglycerides as so as with elevation ofnumbers ofblood pressure indexes in the adolescents ofthe alien ethnogroup. We did not found such kind of links in adolescents of the native ethnogroup that, as we suppose, may be a reflection of the evolutionary developed nutritional stereotype with some predominance oflipid-protein dietary component. Developed through the millennia such kind ofdiet in the indigenous population of the North and Siberia is a response to cold stress and underlies formation ofthe genotype, which aimed to developing a biochemical phenotype with ability to compensate this nutritional atherogenic imbalance.